2007
DOI: 10.1002/elan.200603688
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Graphite Electrodes Modified with Cellobiose Dehydrogenase from the Ascomycete Myriococcum thermophilum

Abstract: The catalytic properties of cellobiose dehydrogenase (CDH) from the ascomycete fungus Myriococcum thermophilum adsorbed on a graphite electrode were investigated for a large variety of carbohydrate substrates. The effects of applied potential, pH and buffer composition were tested and optimized, and the most suitable conditions were used to evaluate the detection limit, linear range, and sensitivity of the sensor for different carbohydrates in the flow injection mode. Subsequently, the long term stability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
115
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 34 publications
11
115
1
2
Order By: Relevance
“…The redox potential of the heme group, the electrochemically active domain of CtCDH acting as the electron donor to the bioanode, is not yet known. However, based on the starting potentials of glucose bioelectrooxidation, on the steady-state potentials of CtCDH-modified SPGEs in the absence and presence of glucose (Table 3), as well as on previous studies of other CtCDHs from different fungi [11,12,14,17,28,32,33], one can assume that the redox potential of the heme group is close to 150 mV versus NHE. The differences between the steady-state potentials of the MvBOx-and CtCDH-SPGEs determine the maximal open circuit potential of the BFC operating in glucose-containing PBS and human serum, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The redox potential of the heme group, the electrochemically active domain of CtCDH acting as the electron donor to the bioanode, is not yet known. However, based on the starting potentials of glucose bioelectrooxidation, on the steady-state potentials of CtCDH-modified SPGEs in the absence and presence of glucose (Table 3), as well as on previous studies of other CtCDHs from different fungi [11,12,14,17,28,32,33], one can assume that the redox potential of the heme group is close to 150 mV versus NHE. The differences between the steady-state potentials of the MvBOx-and CtCDH-SPGEs determine the maximal open circuit potential of the BFC operating in glucose-containing PBS and human serum, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most attractive electrode elements for a potentially implantable BFC is a carbon material, which is cheap, abundant and biocompatible. To design this BFC, SPGE were chosen, as such electrodes are well-characterised [30] and widely used for bioelectrochemical studies of variety of enzymes including different CDH [17,28,31,32] and BOx [20,29], on which both bioelements showed excellent DET-based bioelectrocatalysis (Figures 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellobiose dehydrogenase has been tested in combination with various electrode materials to utilize and enhance DET and increase the current density of CDH bioelectrodes. [26][27][28][29][30] Previous studies applying CDH as the biorecognition element showed promising results, including high current densities (6.84 µA cm -2 ), a good linear range (0.1-30 mM), and a low detection limit (0.05 mM). 31,32 However, until now, no study has investigated the effects of known interfering compounds possibly encountered in vivo.…”
mentioning
confidence: 99%